2018
DOI: 10.1242/jcs.219824
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-like cells reveal novel role of SERPINA1 in transthyretin amyloidosis

Abstract: Transthyretin (TTR)-related familial amyloid polyneuropathy (ATTR) results from aggregation and extracellular disposition of misfolded TTR mutants. Growing evidence suggests the importance of hepatic chaperones for the modulation of pathogenesis. We took advantage of induced pluripotent stem cell (iPSC)-derived hepatocyte-like cells (HLCs) from ATTR patients (ATTR-HLCs) to compare chaperone gene expression to that in HLCs from healthy individuals (H-HLCs). From the set of genes analyzed, chaperones that are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…Plasmin-mediated proteolysis facilitates the process of TTR aggregation, as observed by the increase of TTR aggregated species (909.7 nm; 8.1%) along with the decrease of the soluble form (13.15 nm; 75.4%) (Figure 2B), comparatively to non-digested samples, in which TTR was only found in the soluble form (9.228 nm; 98.5%) (Figure 2A). In addition, TTR V30M incubated with SerpinA1 revealed the presence of soluble particles exhibiting a large diameter (23.81 nm, 100%) (Figure 2C), probably indicating the formation of TTR-SerpinA1 complex, as described previously [33]. Samples incubated with both plasmin and SerpinA1 presented less abundant and smaller TTR aggregates (537.7 nm; 4.3%) (Figure 2D), as compared to samples only incubated with plasmin (Figure 2B).…”
Section: Serpina1 Inhibits In Vitro Transthyretin V30m Aggregation Upon Plasmin-mediated Proteolysissupporting
confidence: 74%
See 3 more Smart Citations
“…Plasmin-mediated proteolysis facilitates the process of TTR aggregation, as observed by the increase of TTR aggregated species (909.7 nm; 8.1%) along with the decrease of the soluble form (13.15 nm; 75.4%) (Figure 2B), comparatively to non-digested samples, in which TTR was only found in the soluble form (9.228 nm; 98.5%) (Figure 2A). In addition, TTR V30M incubated with SerpinA1 revealed the presence of soluble particles exhibiting a large diameter (23.81 nm, 100%) (Figure 2C), probably indicating the formation of TTR-SerpinA1 complex, as described previously [33]. Samples incubated with both plasmin and SerpinA1 presented less abundant and smaller TTR aggregates (537.7 nm; 4.3%) (Figure 2D), as compared to samples only incubated with plasmin (Figure 2B).…”
Section: Serpina1 Inhibits In Vitro Transthyretin V30m Aggregation Upon Plasmin-mediated Proteolysissupporting
confidence: 74%
“…Samples incubated with both plasmin and SerpinA1 presented less abundant and smaller TTR aggregates (537.7 nm; 4.3%) (Figure 2D), as compared to samples only incubated with plasmin (Figure 2B). Besides its function as a serine protease inhibitor, SerpinA1 also functions as an extracellular chaperone and recently, it was reported that SerpinA1 inhibited TTR amyloid Besides its function as a serine protease inhibitor, SerpinA1 also functions as an extracellular chaperone and recently, it was reported that SerpinA1 inhibited TTR amyloid formation in vitro [33]. Thus, the same samples were analyzed by thioflavin T (ThT) assays to evaluate the amyloid nature of the formed species.…”
Section: Serpina1 Inhibits In Vitro Transthyretin V30m Aggregation Upon Plasmin-mediated Proteolysismentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we utilize a patient-specific iPSC-based model of ATTR amyloidosis to investigate the contribution of hepatic proteostasis and disease-modifying factors to the distal toxicity observed in patients. Recent attempts have been made to identify transcriptional differences between ATTR amyloidosis and wild-type iPSC-derived HLCs via qRT-PCR ( Niemietz et al., 2018 ). Problematically, the maturational status of examined cells in these studies was not taken into account, and reported results likely reflect distinct differentiation efficiencies between lines.…”
Section: Introductionmentioning
confidence: 99%